Pendampingan Peternak Kambing di Kampung Muram Sari Distrik Semangga Kabupaten Merauke - Abdul Rizal; Yosehi Mekiuw; Adrianus Adrianus; Silas Tanggu Redu; Ni Wayan Pradnya Paramita; Denvy Meidian Daoed; Wa Ode Suriani (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Muram Sari Village is one of the villages in the Semangga District, Merauke Regency with the third largest population after Muram Sari Village and Marga Mulia Village. This village is dominated by transmigration communities who in fact have a livelihood as farmers and ranchers. One of the livestock developed is goat which is considered to be able to help boost the farmer's economy from generation to generation. Goat farming business is currently being cultivated by breeders, although its implementation is not yet fully maximized. This is due to the lack of knowledge of breeders on the development of goats, the maintenance system is still traditional, maintenance management is not optimal and waste management is not effective. The implementation of assistance can give birth to solutions to solving problems faced by farmers. The implementation of activities includes counseling and technical guidance as a medium for transferring knowledge and technology to farmers, which will be carried out individually. To solve the problems faced by farmers, the solutions offered and will be carried out are through direct discussions about good goat farming, an effective goat housing system, and processing manure waste into organic fertilizer.